Constructing Chinese Identity through the Chinese Language: A Comparative Study of Two Different Secondary Education Systems in Malaysia - Ho, Pei Yao (Animo Repository, 2018)
Chinese Malaysians retain a distinct Chinese identity in a multicultural nation and highly appraise the ethnic-based and cultural importance of the Chinese language. Based on a social psychological perspective, this study employs a survey method with multiple-choice and open-ended questions to examine Chinese identity and the issues of Chinese language from the micro and macro level in two different education systems. By comparing two contrasting educational systems of Independent Chinese Secondary Schools (ICSS) and National Secondary Schools (NSS), this paper with 890 respondents argues that the Chinese identity is constructed through the different degree of learning, using and understanding of Chinese language in the students’ respective educational contexts. Results of statistical analysis reveal significant higher score in NSS sample with a more salient Chinese identity despite having a disadvantaged learning environment for the Chinese language. The comparative analysis sought to provide significant justification and discussion of the Chinese identity construction of Chinese secondary school students.